A scoping review of computational models of the diabetic foot - Yufeng Li; Athia Haron; Chaofan Lin; Yuan Tang; Andrew Weightman; Glen Cooper (PLoS ONE, 2026)
The prevalence of diabetes is expected to be 650 million people by 2030, and diabetic foot ulceration (DFU) is one of its most severe complications. It poses a significant challenge to global health and brings substantial social and economic burdens. Although many studies have explored the mechanisms of DFU development, they are still not fully understood. Due to the high cost of the experimental research, many recent studies have employed the computational modelling approaches to simulate the effects of diabetes on foot tissues from mechanical, thermal, fluid, and cellular perspectives. This study aims to provide a comprehensive review of computational modelling approaches used to investigate various factors influencing DFU, discuss current knowledge gaps and limitations, and outline future research directions. A systematic search was conducted in Web of Science, Scopus, and PubMed databases, identifying a total of N = 1631 records up to March 2025, 31 of which studies met the inclusion criteria and were analysed in this study. Results showed that DFU-related computational models can be categorized into five types: mechanical stress models, thermal models, vascular and nerve system models, multiphysics models, and cellular-based models. These models explore the formation mechanisms of DFU from different perspectives, including biomechanics, temperature, fluid dynamics, HHμm neural signalling, and cellular responses. However, except for mechanical stress models, the other approaches remain in the early stages of development, and the single physics modelling strategies are unable to provide understanding on the coupled processes with the foot and their effect on DFU. Future research should further develop modelling approaches and couple these together to develop comprehensive understanding of DFU pathogenesis.